A Review of Summarizing and Main Idea Interventions for Struggling Readers in Grades 3 Through 12: 1978–2016 - Stevens, Elizabeth A.; Park, Sunyoung; Vaughn, Sharon (Remedial and special education, 2019)
This systematic review examines the effects of summarizing and main idea interventions on the reading comprehension outcomes of struggling readers in Grades 3 through 12. A comprehensive search identified 30 studies published in peer-reviewed journals between 1978 and 2016. Studies included struggling reader participants in Grades 3 through 12; targeted summarizing or main idea instruction; used an experimental, quasi-experimental, or single-case design; and included a reading comprehension outcome. A meta-analysis of 23 group design studies resulted in a statistically significant mean effect of 0.97. Group size, number of sessions, grade level, and publication year did not moderate treatment effect. Visual analysis of six single-case designs yielded strong evidence for retell measures and a range of evidence for short-answer comprehension measures. Findings suggest that main idea and summarizing instruction may improve struggling readers’ main idea identification and reading comprehension. Limitations include the lack of standardized measures and the unreported, changing description of the counterfactual.